The prediction of lung cancer prognosis with blood lipid levels and ratios at the time of diagnosis - Ferhat Arslan; Selim Yalçin; Irfan Karahan (Biomedical and Biotechnology Research Journal, 2022)
Background: Emerging evidence has linked lipid metabolism disorder with lung diseases, but the relationship between blood lipid profile and lung cancer risk is controversial and inconclusive. It was aimed to investigate the relationship of lipid levels and ratios at the time of diagnosis to the prognosis prediction of lung cancer. Methods: Sociodemographic and disease-related clinical characteristics of 92 patients diagnosed with lung cancer were reviewed retrospectively. Patients with available lipid parameters at the time of diagnosis were evaluated. Hemogram parameters of the patients included in the study, creatinine and estimated glomerular filtration rate, alanine aminotransferase level, albumin level, C-reactive protein level, as well as total cholesterol (TC)/high-density cholesterol (HDL) ratio, non-HDL/HDL ratio, low-density lipoprotein/HDL ratio, and triglyceride/HDL ratios were examined. Results: The mean age at presentation was 64.2 ± 9.1 years. The distribution of lung cancers is 6 (6.5%) for small cell lung cancer (SCLC) and 86 (93.5%) for non-SCLC. The median follow-up period of the patients is 12 months. During the follow-up, 63 (68.5%) of the patients died. In the univariate analysis, increased non-HDL/HDL ratio was related to mortality. In multivariate analysis, disease stage, albumin level, and TC level were found to be variables affecting the mortality. Conclusion: TC levels at the time of diagnosis can be a guide in determining the prognosis. More experimental studies are needed to elucidate the relationship between the lipid metabolism and lung cancer etiology and to determine the role of lipid levels and ratios in prognosis prediction.